Benjamin the bear ebook - Spoor, Mike (Animal Fair Values., 2021)
Benjamin has a favorite spot along the river that he thinks belongs only to him, and he doesn't mind snarling at the beavers, salmon, and caribou that come a little too close. But when Benjamin is in trouble, can the other creatures save his life and help the selfish bear realize that the river belongs to everyone?